ANALISIS USABILITY MENGGUNAKAN METODE HEURISTIC EVALUATION PADA APLIKASI TOKO ONLINE - Hera Wasiati; Sudarmanto (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2022)
This study tries to analyze the Usability of the Shopee applications based on the heuristic evaluation method in order to determine the shortcomings of the Shopee applications based on ten heuristic principles. The purpose of this study is to determine the level of user satisfaction in the Shopee applications, as well as to provide advice to those concerned in this case the Shopee applications by recommending the results of the usability evaluation test on the Shopee applications. In this study, the method used to perform Usability analysis on the Shopee applications is by using a questionnaire via Google Form, from the questionnaire a calculation basis is to determine Usability or the user interface in using the Shopee applications. Based on the results of the average percentage of respondents using the heuristic evaluation method on the Shopee applications, the Shopee application has a percentage value of 97.35%. From these results it is known that the level of Usability on the Shopee applications is very good.